VOCATIONAL INTEREST, ATTRIBUTION AND CAREER MATURITY AMONG SECONDARY SCHOOL TEACHERS IN SOKOTO METROPOLIS - Tsagem, Shehu Yahaya; Tambuwal, Malami Umar (Sokoto Educational Review, 2013)
The main thrust of this study was to examine and investigate whether relationships exist among vocational interest, attribution and career maturity among teachers in secondary schools of Sokoto state. Some research questions raised were: Is there any relationship between vocational interest and career maturity of secondary school teachers in Sokoto state: and is there any relationship between vocational interest and attribution of secondary school teachers in Sokoto state? Some null hypotheses generated for the conduct of the study were that: there is no significant relationship between vocational interest and career maturity of secondary school teachers in Sokoto state and there is no significant relationship between vocational interest and attribution of secondary school teachers in Sokoto state. The study used the correlational survey methodology for237 subjects drawn from the total population by means o f simple random sampling technique. Data for the study was collected with the use of an adopted version of Bakare 's Vocational Interest Inventory, an adopted version of Olomolaiye's Self Other Motivation Scale and an adopted version of Crites' Career Maturity Inventory Attitude Scale. Some major findings of the study were that there is a relationship between vocational interest and career maturity and also that there is a relationship between career maturity of secondary school teachers in Sokoto state. Some of the recommendations made were that the Ministry of Education in Sokoto state and the teachers themselves should embark on developing both internal and external inspiring factors toward the general development of the teachers' career maturity thus leading to sound academic effectiveness and that the state Ministry of Education should look for all possible ways to develop teachers' interest and attribution which will eventually enhance the realization of positive and efficient self-esteem, self-efficacy, self-concept and self-fulfillment which are necessary ingredients in career maturity etc.